KEPASTIAN HUKUM EKSEKUSI JAMINAN FIDUSIA TANPA MELALUI PUTUSAN PENGADILAN TERHADAP OBJEK JAMINAN YANG TIDAK DISERAHKAN SECARA SUKARELA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 2/PUU-XIX/2021 - Rahmansyah, Fuad; Maryano, Maryano; TW, Gatut Hendro (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The objectives of this thesis research are: 1) To analyze the execution of fiducia security without a court ruling when the debtor does not voluntarily surrender the collateral object after Constitutional Court Ruling Number 2/PUU-XIX/2021. 2) To analyze the legal certainty for creditors against potential losses arising from the forced execution of fiducia security without a court ruling after Constitutional Court Ruling Number 2/PUU-XIX/202. This study emphasizes the theories of legal certainty and contract law.The research method used is normative juridical research, which involves studying literature or secondary data as the primary source. This is done by conducting a search on the researched issues. The results of this thesis research are: 1) The execution of fiducia security without a court ruling when the debtor does not voluntarily surrender the collateral object after Constitutional Court Ruling Number 2/PUU-XIX/2021 substantially weakens the execution rights for creditors. The researcher argues that the ruling is based on a mistaken and inconsistent understanding of fiducia legal concepts. The researcher asserts that the execution of fiducia security, whether through parate executie or the Implementation of an Executorial Title, is essentially a coercive action to fulfill a defaulting debtor's obligations. The Constitutional Court's ruling, which redefines parate executie as